Analisis Nilai Tambah Pengolahan Tanaman Pegagan (Centella Asiatica) di Usaha Peyek Pegagan Anggun Dicha Snack di Kecamatan Samigaluh Kabupaten Kulonprogo Yogyakarta - Fatihah, Alya; Wulandari, Eliana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Agricultural sector in Indonesia has varieties potential commodities with considerable advantages, such as Gotu Kola (Centella asiatica). Gotu Kola plant is an agricultural commodity that has economic value from its processing in the form of a product with a relatively high selling value. The Dicha Snack home industry is one of the active industries in carrying out business activities processing the Gotu Kola commodity which is located in Samigaluh Sub-District, Kulonprogo District, Yogyakarta. This research aims to analyze the value-added using the Hayami method. The result of the value-added analysis shows, regarding the farming analysis which is processed into peyek pegagan which has a high value-added ratio of 75,13% the BC ratio value is 1,23-1,29, which means the business of processing Gotu Kola is feasible. To increase income of Dicha Snack home industry, it is recommended to expand the offline and online markets to penetrate new customers to increase the sales of peyek pegagan.